2019
DOI: 10.1002/ece3.5431
|View full text |Cite
|
Sign up to set email alerts
|

Parasite infections in a social carnivore: Evidence of their fitness consequences and factors modulating infection load

Abstract: There are substantial individual differences in parasite composition and infection load in wildlife populations. Few studies have investigated the factors shaping this heterogeneity in large wild mammals or the impact of parasite infections on Darwinian fitness, particularly in juveniles. A host's parasite composition and infection load can be shaped by factors that determine contact with infective parasite stages and those that determine the host's resistance to infection, such as abiotic and social environme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 105 publications
(205 reference statements)
1
25
0
Order By: Relevance
“…Therefore, smaller carnivores with shorter lifespans might be more important epidemiologically. Small felids including African wildcat, serval, and caracal are therefore expected to have a higher impact on environmental contamination with Toxoplasma gondii oocysts compared to lions, leopards, and cheetahs [ 3 , 81 , 82 ]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, smaller carnivores with shorter lifespans might be more important epidemiologically. Small felids including African wildcat, serval, and caracal are therefore expected to have a higher impact on environmental contamination with Toxoplasma gondii oocysts compared to lions, leopards, and cheetahs [ 3 , 81 , 82 ]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we investigated the link between each immune measure and individual longevity. For this purpose, we only included juveniles sampled before they reached 12 months of age (Ferreira et al, 2019).…”
Section: Data Analysesmentioning
confidence: 99%
“…Even so, previous studies revealed substantial variation between individuals in terms of their burden of infection with various parasite taxa, the diversity of co-infecting parasite taxa, and how these measures change over time (Irvine et al 2000;Behnke et al 2005;Irvine 2006;Ferreira et al 2019). Individuals differ in their exposure to parasite infective stages, in their ability to mount immune responses to control or clear infections due to factors such as climatic conditions, age, and diet (Cattadori et al 2005;Behnke et al 2005;Råberg et al 2009;Turner and Getz 2010;Hayward et al 2011;Ferreira et al 2019).…”
Section: Section Editor: Elizabeth Marie Warburtonmentioning
confidence: 99%
“…There is also a current lack of non-invasive (fecal) assays for wild mammalian species to measure relevant immunological responses to gastrointestinal parasite infections and how these responses are changed by prevailing conditions such as season, nutrition, and physiological stress throughout an individual’s lifespan (Lee 2006 ; Martin et al 2008 ; Ardia et al 2011 ). Even so, previous studies revealed substantial variation between individuals in terms of their burden of infection with various parasite taxa, the diversity of co-infecting parasite taxa, and how these measures change over time (Irvine et al 2000 ; Behnke et al 2005 ; Irvine 2006 ; Ferreira et al 2019 ). Individuals differ in their exposure to parasite infective stages, in their ability to mount immune responses to control or clear infections due to factors such as climatic conditions, age, and diet (Cattadori et al 2005 ; Behnke et al 2005 ; Råberg et al 2009 ; Turner and Getz 2010 ; Hayward et al 2011 ; Ferreira et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%